The Delaying of Inherited Wealth Distribution and Its Impact: A Case Study of Family Fair in Medan City - Fathul Djannah; Muhammad Rizal (Randwick International of Social Science Journal, 2020)
This study aims to discuss the delaying of inherited wealth distribution and its impact: a case study of family fair in Medan City. This study is field study (field research) which starts from a case that is used as primary data. Then the discussion is supported by secondary data in the form of library research taken from al-Quran and Hadith, fiqh books relating to inheritance issues, including Law NO. 1 of 1974, and Compilation of Islamic Law and other written sources related to it. To get primary data in the field about the case being discussed, the writer interviewed the heirs left by the late Soehermanto. In addition, the authors also interviewed 5 scholars, in this case the authors chose FS UIN SU lecturers who according to the authors are representatives of scholars in Medan City, to explore their opinions on the issue of delaying the distribution of inheritance and its consequences. The result shows that there is a tendency to postpone the distribution of inheritance as has happened in the midst of the community, including in North Sumatera, especially in the city of Medan, which in turn causes injustice and unhappiness in the relationship of brotherhood and kinship. This delay is caused by the lack of knowledge and practice of one's religion, in addition to the system and perspective of the community, including the heirs, especially the children of the heirs, who are always overwhelmed by reluctance, gratitude, fear of being said to be unfilial, and ashamed with the community if "noisy" in matters of inheritance